Emergence of metamagnetic transition, re-entrant cluster glass and spin phonon coupling in Tb2CoMnO6. (28th May 2021) - Anand, Khyati; Pal, Arkadeb; Alam, Mohd.; Dan, Sambhab; Kumar, Shiv; Ghosh, Surajit; Kumari, Seema; Das, A; Sawada, Masahiro; Mohan, Anita; Sathe, Vasant G; Chatterjee, Sandip
Abstract: The double perovskite compound Tb2 CoMnO6 has been investigated using x-ray absorption spectroscopy (XAS), Raman spectroscopy, magnetic measurements and ab initio band structure calculations. It is observed that both anti-ferromagnetic (AFM) and ferromagnetic (FM) phase coexist in this material. The presence of anti-site disorder (ASD) has been established from the analysis of neutron diffraction data. Moreover, a prominent metamagnetic transition is observed in the M ( H ) behavior that has been explained with the drastic reorientation of the pinned domain which are aligned antiparallel by the antiphase boundaries (APBs) at zero field. The ASD further gives rise to spin frustration at low temperature which leads to the re-entrant cluster glass ∼33 K. The coupling between phononic degree of freedom and spin in the system has also been demonstrated. It is observed that the theoretical calculation is consistent with that of the experimentally observed behavior.